Determinants of Satisfaction of Inpatients at Datu Beru Takengon Regional General Hospital - Husnu Gunari; Megawati Megawati; Deli Theo (Newinera Publisher, 2022)
The Datu Beru Takengon Hospital is the location of this research, and its purpose is to investigate the factors that influence patient satisfaction. This study is a quantitative research with a cross-sectional study design, which is a measurement of the dependent variable and the independent variable (age, treatment class, and length of treatment) with the dependent variable (physical appearance, handling, responsiveness, assurance, and empathy (SERVQUAL) and making use of the survey method. According to the findings of the research, the variable guarantee with Exp (B) 25,263 has the most significant link with patient satisfaction, making it the most influential factor that determines the level of satisfaction experienced by patients. Whereas physicians and nurses who have high levels of confidence and trust are 25 times more likely to have the same level of satisfaction as their patients. In this context,